Effect of Adolescent Obesity on Cardiometabolic Risk in African-Americans and Caucasians. (26th December 2012) - Hoffman, Robert P.
Abstract : African-Americans have more hypertension, stroke, and type 2 diabetes than do Caucasians. Endothelial dysfunction and insulin resistance are precursors for each. Since these diseases have origins in pediatrics and are associated with obesity, this study was designed to determine if obesity has different effects on endothelial function, insulin sensitivity, and secretion in African-American and Caucasian adolescents. Thirty-three Caucasian and 25 African-Americans (10–18 years old) were subdivided by BMI into lean, overweight, and obesity groups. Endothelial function was measured as forearm vascular resistance (FVR) over 1 min following 5 min of upper arm vascular occlusion. Insulin sensitivity and secretion were measured using intravenous glucose tolerance test and minimal model. Postocclusive FVR was significantly increased in obese African-Americans. Insulin sensitivity was reduced in obese subjects but did not differ by race. Insulin secretion was increased in African-Americans but did not differ by obesity. Subjects were subdivided into risk groups based on 20th percentile for postocclusion FVR response in lean. Seven of nine obese African-Americans were in the high risk group compared to 0 of 5 obese Caucasians. These results demonstrate that obesity significantly impairs endothelial function in African-Americans. Endothelial dysfunction likely predisposes to future cardiometabolic disease in obese African-American adolescents.